Sleep Problems and Social Impairment in Psychosis: A Transdiagnostic Study Examining Multiple Social Domains - Blanchard, Jack J.; Savage, Christina L. G.; Orth, Ryan D.; Jacome, Anyela M.; Bennett, Melanie E. (Frontiers in Psychiatry, 2020)
Psychotic disorders are characterized by profound social impairment. An accumulation of research has explored the contribution of symptoms, cognitive functioning and behavioral skills deficits to this social dysfunction. Recent research suggests that sleep disturbance has significant social implications in nonclinical populations – this research suggests that sleep problems may also be relevant to understanding social impairment in psychosis. This study adopted a symptom-oriented dimensional approach to examine how sleep disturbance and sleep-related impairment are related to multiple social domains within a transdiagnostic sample of individuals (N = 90). This sample included individuals with a variety of psychotic disorders (n = 75) along with healthy non-clinical participants (n =15) to ensure sampling across the full range of sleep problems and social functioning. Social domains spanned self-reported perceptions of social relationships, social functioning in the community, and behavioral assessments of social competence. We hypothesized that greater sleep disturbance and sleep-related impairment would be associated with more negative or problematic perceptions of social relationships (i.e., less social support, less companionship and greater distress), poorer social functioning in the community, smaller social networks and poorer behavioral ratings of social competency. Results supported these hypotheses indicating that sleep disturbance and sleep impairment have widespread deleterious impacts on perceptions of social relationships, social functioning and competence. Sleep disturbance retained associations with perceptions of social relationships, social functioning, and social competence even after controlling for total symptoms or cognitive functioning. These findings indicate that sleep problems have important implications for fully understanding the causes of social impairment in psychosis.